2015
DOI: 10.1111/ijcp.12721
|View full text |Cite
|
Sign up to set email alerts
|

Identification of components of health complexity on internal medicine units by means of the INTERMED method

Abstract: The INTERMED has the potential to identify a considerable subset of complex internal medicine inpatients for which timely corrective action related to non-biological risk factors not typically uncovered during standard medical evaluations would be considered beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…17,18 The major weakness of the used methods is that the staff workload is conceptualized at a macro level, without taking into account the specific organizational characteristics (e.g., physical layout, information technology available) that may significantly affect workload. 19 When performing their tasks, clinicians and nurses encounter different situations and patients, which are determinants of the situation-and patientlevel workloads. The lack of objectivity in estimation of length activity reinforces the necessity of an instrument that permits a precise measure of staff workloads.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The major weakness of the used methods is that the staff workload is conceptualized at a macro level, without taking into account the specific organizational characteristics (e.g., physical layout, information technology available) that may significantly affect workload. 19 When performing their tasks, clinicians and nurses encounter different situations and patients, which are determinants of the situation-and patientlevel workloads. The lack of objectivity in estimation of length activity reinforces the necessity of an instrument that permits a precise measure of staff workloads.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the use of the INTERMED method demonstrated reliability of results by integrating the biopsychosocial aspects of the disease and its relationship between the patient and the health system, and offering support for case management with the interprofessional team (15) . This method has applications in clinical management (evaluation of case complexity and health needs), in the production of new knowledge (description of different comorbidities, population stratification in randomized clinical trials), education and evaluation of health care outcomes (quality management) (15)(16)(17) .…”
Section: Collection and Organization Of Datamentioning
confidence: 99%
“…Faced with this problem, some studies were conducted with the aims of raising aggravating factors in the health/illness status of elderly patients, improving the quality of care provided to them, and reducing care costs (6)(7)(8)(9)(10)(11) . Some clinical management tools are used to identify biopsychosocial and health system aspects that can improve care for hospitalized elderly, such as the INTERMED method (11)(12)(13)(14)(15)(16)(17) . In Brazil, the application of these tools still lacks research, especially to identify elderly subjects with functional and cognitive limitations, who are generally more susceptible to adverse health outcomes in the context of long-term care (18) .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, our SMH developed an IBD-specific complexity grid (Supplementary Table 3) that was derived from a primary care model. 12 The second component is the use of technology-enhanced care to scale delivery of services in a population health model. Examples of technology in our SMH include the use of telemedicine/telepsychiatry by secure video, health coach virtual visits, remote monitoring, and provider-assisted behavioral interventions that patients can access on their smart phones.…”
Section: Care Coordination and Incorporation Of Technologymentioning
confidence: 99%